Unlocking Sustainable Agriculture: Assessing Readiness, Awareness, and Interventions in Indonesian Oil Palm Smallholders - Jajang Supriatna; Djumarno Djumarno; Ahmad Badawy Saluy; Deden Kurniawan (Migration Letters, 2023)
In pursuit of sustainable agriculture, this study examined the small farmers of Indonesian oil palms, focusing on their readiness, awareness of sustainability, and the impact of social interventions. Data collection involved structured interviews and employed a structure equation model for analysis. Data was collected from 154 respondents through interviews and observation with oil palm farmers using a structured questionnaire and analyzed using SmartPLS version 3.2.9. Before the analysis, seven out of 27 indicators had invalid values. After adjustments, all values met the discriminant validity criteria. Reliability tests confirmed the reliability of the questionnaire, with Cronbach’s alpha > 0.7 for all variables. Discriminant validity requirements were also met. In the inner model analysis, exogenous constructs (smallholder readiness, sustainability awareness, social intervention) collectively explained 68.7% of smallholder sustainability status variance, while smallholder sustainability status was influenced by 55.3%. The relationships between smallholder readiness, sustainability awareness, social intervention and smallholder sustainability status were significant (0.02 ≥ f square < 0.35). Predictive relevance of smallholder readiness, sustainability status, and social intervention in smallholder sustainability status, and smallholder sustainability status in oil palm smallholder performance, was appropriate (Q square > 0.05). The bootstrapping analysis showed significant direct and indirect effects, confirming smallholder readiness, sustainability status, and social intervention as strong predictors of smallholder sustainability status and performance. In conclusion, this study underscores the importance of addressing smallholder readiness for sustainability as a crucial factor in achieving sustainable agriculture goals. More research is needed to explore long-term impacts, external factors, and innovative approaches to smallholder sustainability.